2014
DOI: 10.1108/raf-11-2012-0120
|View full text |Cite
|
Sign up to set email alerts
|

CEO compensation, customer satisfaction, and firm value

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 91 publications
(117 reference statements)
4
20
0
Order By: Relevance
“…Steenkamp (2014) found that the processes and ways in which brand value contributes to firm value differ for different firms. In addition, Fabrizi (2014) found that the chief marketing officer of a company, if correctly incentivised, could contribute more to the value of a company than the chief executive officer, whilst Basuroy et al (2014) found that executive compensation plays an important role in explaining firm value. A superior supply chain management system could also give a company a comparative advantage in value creation (Ellinger et al, 2012).…”
Section: Multiple Regression Analysismentioning
confidence: 99%
“…Steenkamp (2014) found that the processes and ways in which brand value contributes to firm value differ for different firms. In addition, Fabrizi (2014) found that the chief marketing officer of a company, if correctly incentivised, could contribute more to the value of a company than the chief executive officer, whilst Basuroy et al (2014) found that executive compensation plays an important role in explaining firm value. A superior supply chain management system could also give a company a comparative advantage in value creation (Ellinger et al, 2012).…”
Section: Multiple Regression Analysismentioning
confidence: 99%
“…CRM is a philosophy that places the customer at the heart of a business organization's processes, culture and activities to improve customer's satisfaction of services, and maximizes the profits for the organizations (Agarwal, 2009). According to Basuroy et al, (2014) customer satisfaction is an investment, which is considered as an intangible asset to the organizational balance sheet. CEOs wealth on long-term incentives compensation and firm stock prices increases when the customers are satisfied with the products and services offered by the organization.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…They found that there is a positive relationship between equity based compensation and firm value. Although there are very limited studies on equity based compensation and firm value, many researchers suggested that the increase in the level of directors' equity will increase firm value (Fahlenbrach & Stulz, 2009, Basuroy et al, 2014, Wahba et al, 2014.…”
Section: Studies On Relationship Between Directors Remuneration and Firm Valuementioning
confidence: 99%